Humanistic Leadership of School Principals in Promoting Effective Collaboration through Problem-Solving in Madrasah Aliyah - Sri Rahmi; Feiby Ismail; Mardan Umar; Nora Saiva Jannana (Nazhruna: Jurnal Pendidikan Islam, 2025)
This study explores the role of humanistic leadership among school principals in fostering effective collaboration with parents through collaborative problem-solving in Islamic-based schools in East Java. Employing a qualitative approach that involves interviews, observations, and documentation, this research integrates servant leadership principles with Islamic educational values, such as trust, justice, and communal benefit. The study reveals that principals who adopt a humanistic leadership style promote inclusive communication, mutual respect, and shared decision-making with parents, thereby enhancing student motivation, academic performance, and socio-emotional development. The novelty of this research lies in its integration of bibliometric analysis to map current research trends on humanistic leadership in Madrasah Aliyah, identifying key themes, gaps, and underexplored collaborative strategies involving school stakeholders. It uniquely combines theoretical insights from servant leadership and Islamic education with empirical findings from local contexts in East Java, offering a culturally grounded model for inclusive school governance. This study makes a significant contribution to the development of ethical leadership in Islamic education, encouraging school leaders to foster stronger, value-based partnerships with families to enhance educational quality.